Analisis Sektor Unggulan di Kabupaten Bandung Barat Tahun 2014-2018 - Muhamad Rizky Faizal; Asnita Frida Sebayang; Ria Haryatiningsih (UNISBA Press, 2022)
Regional economic development is defined as a process in which local governments and the society manage various resources and form a partnership pattern ti form new jobs and stimulate the development of economic activities in the area. Regional economic growth is one indicator of the success of regional economic development as measured by the amount of GDRP from all sectors. In identifying the regional economic potential economic sector and the potential economic sector, West Bandung Regency is one of the new otonomous regions that have a lot regional economic potential that need attention. This study aims to determine the leading sectors in West Bandung Regency in 2014-2018. The data used in this study is secondary data on GDP based on constant prices for West Bandung Regency and West Java Province in 2014-2018. The research method used in this research is Esteban Marquillas Shift Share analysis and Klassen Typology analysis. Results of the analysis Shift Share method of Esteban Marquillas, it was found that three sectors have competitive advantages an specialization in West Bandung Regency, namely the electricity and gas procurement, real estate and agriculture, forestry, and fisheries sectors. Based on the analysis klassen typology method, it shows that the sector is the provision of accommodation and food and drink, in potential sector, namely the manufacturing sector, sectors that are included in relatively lagging sectors, namely the water supply, waste management, waste and recycling sectors. Pembangunan ekonomi daerah diartikan sebagai proses dimana pemerintah daerah dan masyarakat mengelola berbagai sumber daya dan membentuk suatu pola kemitraan untuk membentuk lapangan pekerjaan baru dan merangsang perkembangan kegiatan ekonomi dalam daerah tersebut. Pertumbuhan ekonomi daerah menjadi salah satu indikator keberhasilan pembangunan ekonomi daerah yang diukur dari besaran nilai PDRB semua sektor. Dalam mengidentifikasi potensi ekonomi daerah, terdapat dua faktor yang perlu diperhatikan, yaitu sektor ekonomi yang unggul dan sektor ekonomi yang potensial, Kabupaten Bandung Barat merupakan salah satu daerah otonom baru yang memiliki banyak potensi ekonomi daerah yang perlu diperhatikan. Penelitian ini bertujuan untuk mengetahui sektor unggulan di Kabupaten Bandung Barat tahun 2014-2018. Data yang digunakan dalam penelitian ini adalah data sekunder PDRB atas dasar harga konstan Kabupaten Bandung Barat dan Provinsi Jawa Barat tahun 2014-2018. Metode penelitian yang digunakan dalam penelitian ini yaitu analisis Shift Share Esteban Marquillas dan analisis Tipologi Klassen. Hasil analisis Shift Share Esteban Marquillas ditemukan tiga sektor yang memiliki keunggulan kompetitif dan spesialisasi di Kabupaten Bandung Barat yaitu sektor pengadaan listrik dan gas, real estat dan pertanian, kehutanan dan perikanan. Berdasarkan analisis Tipologi Klassen menunjukkan sektor yang masuk dalam sektor maju dan tumbuh pesat yaitu sektor pengadaan listrik dan gas, sektor yang masuk dalam sektor potensial yaitu industri pengolahan, sektor yang masuk dalam sektor yang relatif tertinggal yaitu sektor pengadaan air, pengelolaan sampah, limbah dan daur ulang.